Treating atrial fibrillation in the 21st Century: part 2 treatment protocols. (2nd March 2019) - Redpath, Adam; Bowen, Mark
Abstract : Quinidine sulfate remains the drug of choice for the treatment of atrial fibrillation in the horse. Its use involves the application of the prescribing cascade with either the use of 'specials' or imported human medicines. As such, informed client consent should be obtained. A number of adverse events, both cardiovascular and non-cardiovascular, may be observed that can be fatal. Therefore, continuous electrocardiogram (ECG) monitoring should be undertaken throughout treatment. The standard protocol involves 2-hourly dosing with quinidine for four to five doses administered by stomach tube. Adverse events are more likely with increasing doses. Transvenous electrocardioversion is associated with fewer complications when undertaken by experienced operators, but requires specialist equipment. After treatment horses should be assessed, and return to work can be rapid if disease duration was short, but should be delayed in long-standing disease. Ambulatory ECG recordings are valuable in assessing horses following therapy, even in the event of treatment failure.